Design and Testing of a Model of the Effect of Social Situation Appraisal on Social Anxiety in Female University Students with the Mediating Role of Safety Behaviors and Social Beliefs and Thoughts - Hassanvand Amouzadeh, Mahdi (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to design and test a structural model of the effect of social situation appraisal on social anxiety in female university students, with the mediating roles of safety behaviors and social beliefs and thoughts. Methods and Materials: This study employed a descriptive correlational design using structural equation modeling. The statistical population consisted of female students enrolled at Ahvaz Jundishapur University of Medical Sciences during the 2020–2021 academic year, from which 483 participants were selected through convenience sampling. Data were collected using the Social Phobia Inventory (SPIN), the Overall Assessment of the Speaker’s Experience of Stuttering (OASES), the Social Thoughts and Beliefs Scale (STABS), and the Social Phobia Safety Behaviors Scale (SPSBS). After screening for assumptions such as normality and absence of multicollinearity, data were analyzed using AMOS (version 23) with the maximum likelihood estimation method. Indirect effects were examined using the bootstrap procedure. Findings: The results indicated that the final structural model demonstrated acceptable fit indices (RMSEA = 0.07, CFI = 0.98, IFI = 0.98, GFI = 0.97, AGFI = 0.95, χ²/df = 3.75). Social situation appraisal had a significant direct effect on social anxiety (β = 0.84, p < .0001), as well as on safety behaviors (β = 0.63, p < .0001) and social beliefs and thoughts (β = 0.77, p < .0001). In addition, safety behaviors (β = 0.22, p < .0001) and social beliefs and thoughts (β = 0.26, p < .0001) had significant direct effects on social anxiety. Bootstrap analysis confirmed significant indirect effects of social situation appraisal on social anxiety through safety behaviors (β = 0.037, p = .024) and social beliefs and thoughts (β = 0.026, p = .032). Conclusion: The findings support an integrated cognitive-behavioral model in which social situation appraisal influences social anxiety both directly and indirectly through safety behaviors and social beliefs, highlighting the importance of targeting both cognitive and behavioral mechanisms in interventions for socially anxious students.